A Pedagogical Canon for Electric Guitar: An Australian Cultural Perspective - Lee, Daniel A. (Malaysian Journal of Music, 2018)
This study aimed to develop an up-to-date canon for electric guitar for use in popular music education in Australia through research of relevant industry data. A prospective pedagogical canon of ten songs was derived and discussed with suggestions for further curricula content and exemplars proposed. Quantitative and qualitative methodologies were employed to analyse data collected from a variety of industry sources. Findings of the study revealed some enlightening cultural insights from the perspective of Australian music education. The development of electric guitar culture in Australia was shown to be driven by international influences with Australia following the lead from the United States and the United Kingdom rather than offering uniquely Australian input. These factors may have led to a potential stifling of a uniquely Australian electric guitar culture via the widespread use of pedagogical methodologies that have simply adopted international content rather than focussed on development of local input.